2023
DOI: 10.1097/aog.0000000000005105
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Care Utilization and Feasibility of Transurethral Catheter Self-Discontinuation

Abstract: At-home catheter self-discontinuation on the first postoperative day is a feasible option for patients undergoing advanced gynecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The Askew et al, Shatkin-Margolis et al, and Davenport et al studies support that the rate of void trial failure after at-home catheter self-discontinuation is low, even at varying timepoints from surgery (14% failure rate on postoperative day 7, 4 18% failure rate on postoperative day 1, 7 and, 15% on postoperative days 3-4 3 ). This finding helps to support a more flexible, patient-directed approach to determining optimal timing of catheter removal without taking on significant risk.…”
Section: Financial Disclosurementioning
confidence: 93%
See 1 more Smart Citation
“…The Askew et al, Shatkin-Margolis et al, and Davenport et al studies support that the rate of void trial failure after at-home catheter self-discontinuation is low, even at varying timepoints from surgery (14% failure rate on postoperative day 7, 4 18% failure rate on postoperative day 1, 7 and, 15% on postoperative days 3-4 3 ). This finding helps to support a more flexible, patient-directed approach to determining optimal timing of catheter removal without taking on significant risk.…”
Section: Financial Disclosurementioning
confidence: 93%
“…5 Earlier catheter removal reduces UTI risk and patient burden, but these benefits are countered by the concern that earlier removal may carry a higher risk of retention because the bladder has had less recovery time. 5,6 A subsequent study by Davenport and colleagues 7 explored the feasibility of catheter self-discontinuation at home on postoperative day 1 after urogynecologic or minimally invasive gynecologic surgery. This trial demonstrated that at home self-discontinuation on postoperative day 1 resulted in low rates of subsequent retention, with no adverse events seen in this study population.…”
Section: Financial Disclosurementioning
confidence: 99%
“…This was a retrospective cohort study comparing data from the Assessing Healthcare Utilization and Feasibility of Transurethral Catheter Self-discontinuation (FLOTUS) trial with data from a historical cohort obtained via retrospective chart review. 4 Adult women who underwent outpatient urogynecologic surgery and had POUR necessitating discharge with an indwelling urinary catheter with subsequent catheter discontinuation on POD1 were included in this analysis. Women were excluded from the study if their procedure required prolonged catheterization (ie, urethral diverticulectomy, fistula repair, etc) or if there was an intraoperative complication necessitating catheterization such as a cystotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, FLOTUS was a prospective cohort study performed at our institution examining health care utilization and surgical complications in 50 patients who failed the immediate postoperative VT on the day of advanced gynecologic and urogynecologic surgery between August 2021 and January 2022. 4 Details of our institutional procedures for performing VTs appear as follows. Participants subsequently performed at-home CSD followed by an autofill VT on POD 1.…”
Section: Methodsmentioning
confidence: 99%
“…An author's name is misspelled in the byline in the article by Davenport et al 1 in the April 2023 issue. “Emily Melvin” is incorrect.…”
mentioning
confidence: 99%